2024
DOI: 10.1039/d3sm01124k
|View full text |Cite
|
Sign up to set email alerts
|

1H-NMR studies on the volume phase transition of DNA-modified pNipmam microgels

Rebecca Hengsbach,
Gerhard Fink,
Ulrich Simon

Abstract: DNA functionalized pNipmam microgels, which have recently been introduced, are examined at different concentrations of sodium chloride and in PBS solutions via temperature dependent 1H-NMR measurements and are compared to pure pNipmam microgels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The preparation and characterization of P(NIPAm-co-NIPMAm)/chitosan core/shell nanohydrogels, capable of drug release at different temperatures and pH levels, were reported [51]. Recently, it was shown that DNA modification reduces the volume phase transition temperature of PNIPMAm microgels, which could be further lowered by salt [52].…”
Section: Poly(n-isopropylmethacrylamide)mentioning
confidence: 99%
“…The preparation and characterization of P(NIPAm-co-NIPMAm)/chitosan core/shell nanohydrogels, capable of drug release at different temperatures and pH levels, were reported [51]. Recently, it was shown that DNA modification reduces the volume phase transition temperature of PNIPMAm microgels, which could be further lowered by salt [52].…”
Section: Poly(n-isopropylmethacrylamide)mentioning
confidence: 99%